AKTA KELAHIRAN ANAK LUAR KAWIN SEBAGAI HAK PERDATA ANAK - Maria Rosalina (Jurnal Hukum dan Kemasyarakatan Al-Hikmah, 2020)
Abstract Marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on the One Godhead. One of the goals of marriage is to have offspring, namely children, who are the successors of the family. Article 2 Paragraph (2) Law No. 1 Year 1974 states "Every marriage is recorded according to the prevailing laws and regulations." Therefore, based on Article 2 Paragraph (2), marriages that are not registered at the agency in charge of this are illegitimate in state administration, and children who born from this marriage are children outside of marriage. In Islamic law, there is no distinction between out-of-wedlock children and adulterous children, because according to Islamic law, children born from adultery, religious marriage or unmarried marriage are considered children born out of wedlock because their marriage is not registered. Article 27 Paragraph (1) and (2) of Law Number 23 of 2002, as amended by Law Number 35 of 2014 concerning Child Protection, it can be concluded that since birth, every child has the right to obtain a personal identity as set forth in a deed. birth, regardless of whether the child is legal or illegitimate. If an Indonesian citizen wishes to register the birth of his child, then he must meet the requirements stated in Article 33 of Presidential Decree No. 96 of 2018 concerning Requirements and Procedures for Population Registration and Civil Registration. Furthermore, Article 34 of Presidential Decree No. 96 of 2018 states that residents can make a statement of absolute responsibility (SPTJM) for the correctness of the data with the knowledge of 2 (two) witnesses in case: a. Do not have a birth certificate; and or b. Do not have a marriage book / marriage certificate quotation or other valid evidence but the relationship status in the KK shows as husband and wife.The Medan City Government, at the Meda City Civil Registry Office, the requirements for obtaining a birth certificate, apart from applying the Presidential Decree No. 96 of 2018 concerning Requirements and Procedures for Population Registration and Civil Registration, also divides the processing of a birth certificate into 2 (two) parts of the application for a birth certificate, namely based on the age of birth from the age of 0 to 60 days and the age of 60 days and above. Keyword : Birth Certificate, Unmarried Children, Civil Rights.Abstrak Perkawinan merupakan ikatan lahir batin antara seorang pria dengan seorang wanita sebagai suami isteri dengan tujuan membentuk keluarga atau rumah tangga yang bahagia dan kekal berdasarkan Ketuhanan Yang Maha Esa. Salah satu tujuan dari perkawinan adalah untuk memperoleh keturunan yaitu anak, yang merupakan penerus keluarga tersebut. Pasal 2 Ayat (2) UU No. 1 Thn 1974 menyebutkan “Tiap-tiap perkawinan dicatat menurut peraturan perundang-undangan yang berlaku”.Berdasarkan Pasal 2 Ayat (2) ini, perkawinan yang tidak dicatatkan pada instansi yang bertugas untuk itu adalah tidak sah secara administrasi negara, dan anak yang lahir dari perkawinan tersebut merupakan anak luar kawin. Dalam hukum Islam, tidak membedakan antara anak luar kawin maupun anak zina, karena menurut hukum Islam, anak yang dilahirkan dari perzinaan, pernikahan secara agama atau nikah siri, dianggap sebagai anak yang lahir di luar kawin karena pernikahannya tidak dicatatkan. Pasal 27 Ayat (1) dan (2) Undang-undang Nomor RI 23 Tahun 2002, sebagaimana yang telah dirubah dengan Undang-undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak dapat disimpulkan bahwa setiap anak sejak kelahirannya berhak untuk mendapatkan identitas diri yang dituangkan dalam akta kelahiran, tanpa melihat apakah anak tersebut anak sah atau anak luar kawin. Jika seorang Warga Negara Indonesia hendak mencatatkan kelahiran anaknya, maka harus memenuhi persyaratan yang disebutkan pada Pasal 33 Perpres No. 96 Tahun 2018 Tentang Persyaratan dan Tata Cara Pendaftaran Penduduk dan Pencatatan Sipil. Selanjutnya Pasal 34 Perpres No. 96 Tahun 2018 ini menyebutkan penduduk dapat membuat surat pernyataan Jurnal Hukum dan Kemasyarakatan Al-Hikmah Vol. 1 No. 1, September 2020 176 tanggung jawab mutlak (SPTJM) atas kebenaran data dengan diketahui oleh 2 (dua) orang saksi dalam hal: a.Tidak memiliki surat keterangan kelahiran; dan atau b. Tidak memiliki buku nikah/kutipan akta perkawinan atau bukti lain yang sah tetapi status hubungan dalam KK menunjukan sebagai suami istri. Pemerintah Kota Medan, pada Dinas Kependudukan Catatan Sipil Kota Meda,syarat untuk pengurusan akta kelahiran, selain berlaku Perpres No. 96 Tahun 2018 Tentang Persyaratan dan Tata Cara Pendaftaran Penduduk dan Pencatatan Sipil, juga membagi pengurusan akta kelahiran menjadi 2 (dua) bagian permohonan akta kelahiran yaitu berdasarkan usia kelahiran dari usia 0 sampai dengan 60 hari dan usia 60 hari hari keatas. Kata Kunci : Akte Kelahiran, Anak Luar Kawin, Hak Perdata